2008
DOI: 10.1897/ieam_2007-073.1
|View full text |Cite
|
Sign up to set email alerts
|

A multitrophic approach to monitoring the effects of metal mining in otherwise pristine and ecologically sensitive rivers in Northern Canada

Abstract: It is not known if current chemical and biological monitoring methods are appropriate for assessing the impacts of growing industrial development on ecologically sensitive northern waters. We used a multitrophic level approach to evaluate current monitoring methods and to determine whether metal-mining activities had affected 2 otherwise pristine rivers that flow into the South Nahanni River, Northwest Territories, a World Heritage Site. We compared upstream reference conditions in the rivers to sites downstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Their results indicated that metal and nutrient concentrations along Prairie Creek either remained at upstream reference levels or were elevated at the near‐field site and then back within upstream reference concentrations at the far‐field site. Along Flat River, Spencer et al () found that concentrations of metals and nutrients at the near‐field and far‐field sites were either both consistently elevated above upstream reference concentrations or concentrations continued to increase at the far‐field site. Bowman et al () compared near‐field and far‐field sites to regional reference sites and generally found a decreasing trend in metal and nutrient concentration from near‐field to far‐field sites along Prairie Creek.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their results indicated that metal and nutrient concentrations along Prairie Creek either remained at upstream reference levels or were elevated at the near‐field site and then back within upstream reference concentrations at the far‐field site. Along Flat River, Spencer et al () found that concentrations of metals and nutrients at the near‐field and far‐field sites were either both consistently elevated above upstream reference concentrations or concentrations continued to increase at the far‐field site. Bowman et al () compared near‐field and far‐field sites to regional reference sites and generally found a decreasing trend in metal and nutrient concentration from near‐field to far‐field sites along Prairie Creek.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we develop reference condition models for the South Nahanni River Watershed using 3 descriptors of benthic algal communities (algal taxonomy, diatom taxonomy, and algal pigments) from a total of 62 undisturbed regional reference river sites, apply them at river sites adjacent to and downstream of 2 metals mines, and compare results of the assessments to longitudinal patterns in water chemistry which include use of water physicochemistry data to determine potential zones of impairment downstream of each mine. We predicted that RCA models would identify impairment at some sites downstream of each mine, given marked increases in concentrations of some metals and nutrients adjacent to and immediately downstream of mine discharges (Scrimgeour et al ; Thomas et al ) and strong relations between variance in algal community structure and water physicochemistry (Spencer et al ; Thomas et al ). We also anticipated differences in site assessments when algal communities were defined using the 3 community descriptors, because they reflect different components of the overall benthic algal community (i.e., taxonomy of all algal species vs solely diatoms) and differ in the ways that they are described (i.e., taxon percent abundance vs concentrations of pigments).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreases in the diversity of the assemblage when under stress have been reported (such as Patrick & Reimer, 1966;Sabater, 2000;Gold et al, 2003;Spencer et al, 2008), although it has to be considered that the diversity indices for the benthic diatom assemblages are very variable, and no authors have described a direct cause-effect relationship between chemical pollution and diversity (Ricciardi et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The survey and analysis of ecological risk assessment in decision making shows that such assessments have been most effective when clear management goals were included in the problem formulation; translated into information needs; and, developed in collaboration with decision makers, assessors, scientists, and stakeholders. Spencer et al (2008) used a multitrophic level approach to evaluate current monitoring methods and to determine whether metal-mining activities had affected two otherwise pristine rivers that flow into the South Nahanni River, Northwest Territories, a World Heritage Site. Their results showed that although the effects of mining activities on riverine biota currently are limited, there is potential for effects to occur with proposed growth in mining activities.…”
Section: Ecologicalmentioning
confidence: 99%